Case report: Application of three-dimensional technologies for surgical treatment of portosystemic shunt with segmental caudal vena cava aplasia in two dogs - Kang, Jinsu; Yang, Myungryul; Kwon, Yonghwan; Jeong, Chorok; Kim, Namsoo; Heo, Suyoung (Frontiers in Veterinary Science, 2022)
This case report describes the application of three-dimensional (3D) technologies for the surgical treatment of portosystemic shunt (PSS) with segmental caudal vena cava (CVC) aplasia. Two client-owned dogs were diagnosed with PSS along with segmental CVC aplasia using computed tomography. Through 3D volume and surface rendering, the vascular anatomic anomaly of each patient was identified in detail. A patient-specific 3D vascular model was used for preoperative planning. According to the plan established based on the 3D rendered image and printed model, shunt occlusion was performed using cellophane banding in the first case. An ameroid constrictor was used in the second case. Both patients showed good recovery without any clinical symptoms or complications. The use of 3D technologies in small animals has many advantages, and its use in vascular surgery, as in these cases, is also a therapeutic option worth considering.